1994
DOI: 10.1038/ki.1994.192
|View full text |Cite
|
Sign up to set email alerts
|

Anti-platelet therapy in graft thrombosis: Results of a prospective, randomized, double-blind study

Abstract: Hemodialysis (HD) vascular access thrombosis remains a major cause of morbidity, accounting for 17.4% of all HD patient hospital admissions in 1986. We initiated this prospective, randomized, double-blind, placebo-controlled, parallel group study to examine if dipyridamole and/or aspirin decreased the rate of thrombosis of expanded polytetrafluoroethylene (ePTFE) grafts in HD patients. Two patient groups were studied: Type I--with a new ePTFE graft; and Type II--with thrombectomy and/or revision of a previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
3
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(152 citation statements)
references
References 39 publications
3
142
3
4
Order By: Relevance
“…A small randomized clinical trial reported that dipyridamole with or without aspirin, but not aspirin alone, reduced graft thrombosis. 8 However, larger studies of aspirin alone or in combination with another anti-platelet agent have reported trends for aspirin to improve graft patency. 9 -11 The Dialysis Outcomes and Practice Patterns Study (DOPPS) found that treatment with aspirin was associated with a 16% (P ϭ 0.069) reduction in the adjusted relative risk for loss of primary graft patency and a 30% (P Ͻ 0.001) lower risk of loss of cumulative graft patency.…”
Section: Discussionmentioning
confidence: 99%
“…A small randomized clinical trial reported that dipyridamole with or without aspirin, but not aspirin alone, reduced graft thrombosis. 8 However, larger studies of aspirin alone or in combination with another anti-platelet agent have reported trends for aspirin to improve graft patency. 9 -11 The Dialysis Outcomes and Practice Patterns Study (DOPPS) found that treatment with aspirin was associated with a 16% (P ϭ 0.069) reduction in the adjusted relative risk for loss of primary graft patency and a 30% (P Ͻ 0.001) lower risk of loss of cumulative graft patency.…”
Section: Discussionmentioning
confidence: 99%
“…In both the univariate and multivariable analyses, ASA use was associated with a decrease in the risk of graft thrombosis. Sreedhara et al (39) conducted a randomized trial comparing ASA to dipyridamole alone, ASA plus dipyridamole, and placebo and compared time to thrombosis. ASA was associated with an increased the risk of thrombosis (relative risk, 1.99; P ϭ 0.18) in incident grafts versus the protective effect associated with use of dipyridamole (relative risk, 0.35; P ϭ 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…In a single-center, double-blinded RCT, dipyridamole decreased AVG thrombosis by approximately 50% (30). A much larger, multicenter, double-blinded RCT observed that aspirin plus long-acting dipyridamole improved primary unassisted AVG survival by approximately 18% (31).…”
Section: Antiplatelet Agentsmentioning
confidence: 99%